Audit on Drug Screening Practice on Inpatient Psychiatric Wards - Mohamed Hamid; Mohamed Ahmed; Mythreyi Shekar (BJPsych Open)
Aims: The relationship between mental illness and substance misuse is well established. Early identification through drug testing can inform more holistic management plans. This audit aims to check the compliance of the current practice on acute psychiatric wards with the Trust policy for drug screening, it also aims to draw conclusions, and recommend changes to increase the compliance and benefits from implementing the policy.